Discovery of Streptococcus pneumoniae serogroup 35 variants in Australian patients. (July 2017) - Staples, M.; Graham, R.M.A.; Hicks, V.; Strachan, J.; Gonçalves da Silva, A.; Peverall, J.; Wicks, V.; Jennison, A.V.
Abstract: Objectives: Streptococcus pneumoniae isolates from Australian invasive pneumococcal disease cases displaying an atypical 35B phenotype. Whole genome sequencing was used to analyse these strains and identify changes to the capsule gene regions. Methods: Four atypical serogroup 35 isolates from Australian reference laboratories were unable to be assigned to one of the four known group 35 serotypes by the Quellung serotyping method. Genetic characterization of the capsule locus was performed by bioinformatic analysis of whole genome sequencing data for all isolates. Results: Genetic analysis identified four independent disruptions to the wciG gene, which encodes an O -acetyltransferase responsible for the O -acetylation of the 6Galβ1 residue in the capsular polysaccharide repeat unit of serotype 35B. Conclusions: This is the first published report on the incidence and capsular gene characteristics of a S. pneumoniae 35B variant.